Photosystem I is tolerant to fluctuating light under moderate heat stress in two orchids Dendrobium officinale and Bletilla striata. (February 2021) - Yang, Ying-Jie; Tan, Shun-Ling; Sun, Hu; Huang, Jia-Lin; Huang, Wei; Zhang, Shi-Bao
Highlights: We examine responses of PSI and PSII to FL at 42 °C in D. officinale and B. striata . FL at 42 °C induces selective photoinhibition of PSII in these two orchids. The water-water cycle protects PSI in FL at 42 °C in D. officinale . Heat-induced PSII photoinhibition protects PSI in FL at 42 °C in B. striata . WWC and PSII photoinhibition are important strategies to cope with FL at 42 °C. Abstract: Under natural field conditions, plants usually experience fluctuating light (FL) under moderate heat stress in summer. However, responses of photosystems I and II (PSI and PSII) to such combined stresses are not well known. Furthermore, the role of water-water cycle (WWC) in photoprotection in FL under moderate heat stress is poorly understood. In this study, we examined chlorophyll fluorescence and P700 redox state in FL at 42 °C in two orchids, Dendrobium officinale (with high WWC activity) and Bletilla striata (with low WWC activity). After FL treatment at 42 °C, PSI activity maintained stable while PSII activity decreased significantly in these two orchids. In D. officinale, the WWC could rapidly consume the excess excitation energy in PSI and thus avoided an over-reduction of PSI upon any increase in illumination. Therefore, in D. officinale, WWC likely protected PSI in FL at 42 °C. In B. striata, heat-induced PSII photoinhibition down-regulated electron flow from PSII and thus prevented an over-reduction of PSI after transition from low to high light. Consequently, in B. striata moderate PSII photoinhibition could protected PSI in FL at 42 °C. We conclude that, in addition to cyclic electron flow, WWC and PSII photoinhibition-repair cycle are two important strategies for preventing PSI photoinhibition in FL under moderate heat stress.